INDONESIA Implementasi Inovasi Media Pembelajaran oleh Guru Di TK Al-Islah Gorontalo dalam Meningkatkan Keterlibatan Anak Didik - Sindi Baco; Novianty Djafri; Pupung Puspa Ardini; Mohamad Zubaidi (Irfani, 2026)
This study aims to describe the implementation of innovative learning media by teachers at TK Al-Islah Gorontalo and to examine its influence on students' active engagement. This research employed a qualitative descriptive approach using observation, semi-structured interviews, and documentation involving six informants consisting of one school principal and five classroom teachers. The findings reveal that teachers have applied various innovative media, including digital-based media (thematic videos, interactive PowerPoint, and educational application-based games) and local material-based media (cardboard, used bottles, and flannel teaching aids). These innovations enhanced children's motivation, attention, and active participation. Key supporting factors include school leadership support, available facilities, and teacher collaboration, while challenges involve limited time, insufficient ongoing training, and technical constraints. Innovation diffusion occurs gradually through professional collaboration and best practice sharing among teachers. Overall, the implementation of innovative learning media significantly contributed to improving learning quality and children's active engagement at TK Al-Islah Gorontalo